Soil and canopy contributions in a predictive model of aerial biomass in the Pampa Biome - Terra, Fabrício da Silva; Fonseca, Eliana Lima da; Saldanha, Dejanira Luderitz (Pesquisa Agropecuaria Brasileira, 2011)
. 4 and 3, 4 and 5, 4 and 7 bands, of Landsat 7/ETM+ sensor – were suggested in order to represent the spectral contribution of the different underlying soils and the influence of canopy structural differences. The spectral component parameterization was implemented by multiple linear regression and, then, it was compared to the biomass data measured in the field. Spectral variables that better describe the variations of initial biomass availability and soil spectral contributions were the soil fraction (spectral mixture linear model), and ratio between 4 and 7 bands. The spectral component of the JONG model, with the new parameterization, showed sensibility in eliminating the canopy and soil influences in the biomass initial availability and, also, improved the interpretation of results due to the relationship between selected spectral variables.
Keywords: forage availability; Landsat; agrometeorological-spectral model; spectral variables